Can agricultural citizen science improve seed systems? The contributions of crowdsourcing participatory variety selection through on-farm triadic comparisons of technologies - Bessette, Guy (CGIAR Research Program on Grain Legumes and Dryland Cereals, 2018)
Using on-farm triadic comparisons of technologies (tricot) for crowdsourcing participatory variety selection is a new citizen–science methodology for agriculture. Developed by Bioversity International as part of a programme known as Seeds for Needs, it allows large numbers of farmers to test different technologies on their farms. Farmers receive packages of seeds with a different combination of three different varieties, randomly selected from a large and diverse set of varieties to be tested. They submit their feedback in simple format, ranking the ‘best / middle / worst’ of each package for different traits. These farmer-generated data are then combined with environmental and socioeconomic data and analyzed with specific, novel statistical methods for ranking. Based on a review of several years of crowdsourcing experience in countries around the world, this report summarizes the different features and contributions of the tricot methodology to improve the functionality of seed systems.